2011
DOI: 10.1073/pnas.1017700108
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the RNA binding domains of Ser-Arg splicing factor 1 and U1-70K snRNP protein determines early spliceosome assembly

Abstract: It has been widely accepted that the early spliceosome assembly begins with U1 small nuclear ribonucleoprotein (U1 snRNP) binding to the 5′ splice site (5′SS), which is assisted by the Ser/Arg (SR)-rich proteins in mammalian cells. In this process, the RS domain of SR proteins is thought to directly interact with the RS motif of U1-70K, which is subject to regulation by RS domain phosphorylation. Here we report that the early spliceosome assembly event is mediated by the RNA recognition domains (RRM) of serine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
217
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(236 citation statements)
references
References 32 publications
6
217
2
Order By: Relevance
“…Another prominent FUS target is the conserved intron of the gene coding for the small nuclear ribonucleoprotein 70 kDa polypeptide (snRNP70, U1-70K) (Fig. 3A), which is an essential component of the U1 snRNP that is required for recognition of the 5 ′ splice site during spliceosome assembly (Kohtz et al 1994;Cho et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Another prominent FUS target is the conserved intron of the gene coding for the small nuclear ribonucleoprotein 70 kDa polypeptide (snRNP70, U1-70K) (Fig. 3A), which is an essential component of the U1 snRNP that is required for recognition of the 5 ′ splice site during spliceosome assembly (Kohtz et al 1994;Cho et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…additional splicing factors (31). In addition, phosphorylation of the RS region has been shown to stabilize its structure and decrease its conformational entropy (32).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relatively small size of the domain, it is unlikely that it would act on splicing by recruiting spliceosome components. Indeed, it was reported recently that both RRMs of SRSF1 are required to interact with U1-70K (32). A more tempting hypothesis could be that the pseudo-RRM regulates splicing by competing for RNA binding with one or several splicing factors.…”
Section: Srsf1 (Sf2/asf)mentioning
confidence: 99%
“…However, in some cases, this domain also can be dispensable for constitutive and enhancer-dependent splicing (31), indicating a key function of the RRMs in this process. Although previously it was shown that the RRMs of SRSF1 can contact the spliceosomal component U1-70K directly (32), the main role of the RRMs seems to be to provide RNAbinding specificity and to dictate the position of SR proteins on pre-mRNAs (18).…”
mentioning
confidence: 99%